2019
DOI: 10.1001/jamapediatrics.2018.3227
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Pediatric Clinical Trials Submitted to the US Food and Drug Administration

Abstract: IMPORTANCE The increasing prevalence of pediatric chronic disease has resulted in increased exposure to long-term drug therapy in children. The duration of recently completed drug trials that support approval for drug therapy in children with chronic diseases has not been systematically evaluated. Such information is a vital first step in forming safety pharmacovigilance strategies for drugs used for long-term therapy in children. OBJECTIVE To characterize the duration of clinical trials submitted to the US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…While policy and legislation have contributed to childhood cancer drug approvals in the United States, the lack of evidence on drug safety and efficacy evidence is still concerning. 4 Previous research has pointed out that 61% of clinical trials submitted to support FDA approvals of drugs for paediatric use were shorter than 1 year, 56 which is one-third of the median study duration for overall survival endpoints used to approve adult cancer indications. 57 We found that approvals of paediatric indications of targeted medications were mainly supported by single arm pivotal trials with various efficacy outcomes.…”
Section: Approvals Of Childhood Cancer Drugs In China and The United Statesmentioning
confidence: 99%
“…While policy and legislation have contributed to childhood cancer drug approvals in the United States, the lack of evidence on drug safety and efficacy evidence is still concerning. 4 Previous research has pointed out that 61% of clinical trials submitted to support FDA approvals of drugs for paediatric use were shorter than 1 year, 56 which is one-third of the median study duration for overall survival endpoints used to approve adult cancer indications. 57 We found that approvals of paediatric indications of targeted medications were mainly supported by single arm pivotal trials with various efficacy outcomes.…”
Section: Approvals Of Childhood Cancer Drugs In China and The United Statesmentioning
confidence: 99%
“…The assumption that children presenting conditions similar to adults will respond similarly to treatment has led to the use of many medications approved for adults to treat children, without appropriate studies to justify such use 1 . This may result in therapeutic failure or toxic effects attributed to the differences between children and adults in drug pharmacokinetics and pharmacodynamics, different stages of ontogenesis of drug receptors, and immaturity of biotransformation pathways 2 . This kind of off‐label drug use has developed as an important issue worldwide 3,4 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…This section of the Reflection Paper acknowledges the benefits of continuing to address residual scientific uncertainties in the target population even once efficacy and a positive risk‐benefit having been established. Given the potential long‐term exposure of patients to these drugs, it is essential to consider whether new approaches are needed to better understand the safety of long‐term use of these drugs . Examples might be where long‐term follow‐up studies are required to address uncertainties related to growth and maturation and specific uncertainties related to the understanding of therapeutic efficacy and/or safety that have implications for understanding the benefit‐risk of a medicine with the potential to inform better use of the medicine in clinical practice.…”
Section: Proposed Frameworkmentioning
confidence: 99%